Laws of Waterville College, Maine 11 (1832) - (:unkn) unknown (General Publisher, 1832)
Banned students from keeping firearms or any deadly weapon whatsoever on campus; also banned bring gunpowder on campus.
--
Keywords: SENSITIVE PLACES